2014
DOI: 10.3928/01477447-20140401-08
|View full text |Cite
|
Sign up to set email alerts
|

Infection After Primary Total Hip Arthroplasty

Abstract: The number of primary total hip arthroplasties (THAs) performed in the United States each year continues to climb, as does the incidence of infectious complications. The changing profile of antibiotic-resistant bacteria has made preventing and treating primary THA infections increasingly complex. The goal of this review was to summarize (1) the published data concerning the risk of surgical site infection (SSI) after primary THA by type of bacteria and (2) the effect of potentially modifying factors. The Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
53
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 48 publications
(202 reference statements)
2
53
1
1
Order By: Relevance
“…Infection rates after TJA are dependent on many factors including patient comorbidities, operative time, operating room environment, and perioperative risk reduction interventions [3,8,[27][28][29][30][31][32][33][34][35][36]. Reported rates of PJI after TJA are highly variable and range from 0.5% to 3.3% in the early postoperative period [1,[3][4][5]28,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection rates after TJA are dependent on many factors including patient comorbidities, operative time, operating room environment, and perioperative risk reduction interventions [3,8,[27][28][29][30][31][32][33][34][35][36]. Reported rates of PJI after TJA are highly variable and range from 0.5% to 3.3% in the early postoperative period [1,[3][4][5]28,37].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, PJI occurred in only 4 of 1,053 TJA patients. Conclusion: We found that formation of an IRC focused on evaluating and implementing strategies to reduce PJI following TJA can be effective.Periprosthetic joint infection (PJI) after total joint arthroplasty (TJA) is a significant complication associated with substantial morbidity and cost [1][2][3][4][5]. There are multiple risk factors that increase a patient's likelihood for developing a PJI: comorbidities, preoperative care, surgical factors, and postoperative factors.…”
mentioning
confidence: 99%
“…These infections occur after 0.4% to 2.2% primary THAs and TKAs [24,25,46]. For patients undergoing tumor megaprosthetic implantation, the risk is greater, estimated at 4% to 45% [28].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of infectious complications occurring after surgical implant placement reaches 3 to 12 per cent [6], while surgical site infections (SSI) following the replacement of big joints is observed in 2.5 per cent of cases [7], in addition, the risk of periprosthetic infection increases 3.3 times in case of revisional prosthetic repair [8]. The number of joint replacement surgeries is on the rise across the world, however the incidence of infectious complications associated with this kind of intervention gains even more momentum [9].…”
Section: Introductionmentioning
confidence: 99%